Development of Busy Book Learning Media in Improving Children's Literacy Skills in Group B of Aisyiyah Bustanul Athfal V Kindergarten - Zulkaida, Karima; Agusniatih, Andi; Fitriana, Fitriana; Gagaramusu, Yusdin Bin Mahmudin (Journal of Educational Sciences, 2025)
The problem in this study lies in children's literacy skills. This study aims to determine the development of busy book learning media in improving the literacy skills of children in Group B. This study was conducted at Aisyiyah Bustanul Athfal V Kindergarten with the research subjects being children in Group B1. The method used in this study was Research and Development (R&D) to determine (1) the development of busy book learning media in improving literacy skills, and (2) the effectiveness of busy book media in improving literacy skills. Based on the assessment of media and language experts, it was tested on children in group B1. The model used in research and development was the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). According to the assessment of media experts, the score was 91.6% with a category of highly valid, and the assessment of language experts showed 95.8% with a category of highly valid. After testing the children in three aspects, namely vocabulary, answering questions, and retelling stories, the results showed that the Busy Book Learning Media in Improving Literacy Skills was deemed feasible with a category of highly valid and could improve the literacy skills of children in Group B aged 5-6 years.